2022
DOI: 10.1093/narcan/zcac032
|View full text |Cite
|
Sign up to set email alerts
|

Escape from G1 arrest during acute MEK inhibition drives the acquisition of drug resistance

Abstract: Mutations and gene amplifications that confer drug resistance emerge frequently during chemotherapy, but their mechanism and timing are poorly understood. Here, we investigate BRAFV600E amplification events that underlie resistance to the MEK inhibitor selumetinib (AZD6244/ARRY-142886) in COLO205 cells, a well-characterized model for reproducible emergence of drug resistance, and show that BRAF amplifications acquired de novo are the primary cause of resistance. Selumetinib causes long-term G1 arrest accompani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Previously, the role of DNA replication was demonstrated in the mechanisms governing the resistance of BRAFV600E-mutated colon cancer cells to the MEK inhibitor selumetinib [ 31 ]. It was shown that acquisition of MEK inhibitor resistance arose through de novo BRAFV600E amplification resulting from DNA replication during prolonged selumetinib treatment [ 31 ]. The same study also revealed that decreasing the frequency of DNA replication during selumetinib treatment suppressed the emergence of resistant clones.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the role of DNA replication was demonstrated in the mechanisms governing the resistance of BRAFV600E-mutated colon cancer cells to the MEK inhibitor selumetinib [ 31 ]. It was shown that acquisition of MEK inhibitor resistance arose through de novo BRAFV600E amplification resulting from DNA replication during prolonged selumetinib treatment [ 31 ]. The same study also revealed that decreasing the frequency of DNA replication during selumetinib treatment suppressed the emergence of resistant clones.…”
Section: Discussionmentioning
confidence: 99%